2003
DOI: 10.1260/147807703771799148
|View full text |Cite
|
Sign up to set email alerts
|

The Tangible Interface: Experiments as an Integral Part of a Research Strategy

Abstract: The Human-Computer interface is crucial to good design support tools. It has to be non-interruptive and non-distracting, yet allow the architect to interact with the computer software.The physical reality of the interface, such as the shape and manipulability of devices like the mouse, keyboard, joystick, or dataglove, has to be mapped on actions and commands in the software. Already the current user interfaces are felt to be inadequate for a good support of design, and the functionality of design tools is gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our tangible design support system is related to previous research on design support tools [2,9] and TUIs for design support [4,5,6,10,12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our tangible design support system is related to previous research on design support tools [2,9] and TUIs for design support [4,5,6,10,12].…”
Section: Related Workmentioning
confidence: 99%
“…There are tools to attempt to aid the designer by intelligently searching the design space within the confines of the design goals and constraints [4,5,10]. For example, a system called Urp (a luminous tangible workbench for urban planning and design) combined and integrated twodimensional drawings, physical models, and digital models to help urban designers and decision makers visualize light, shadows, and wind velocity around groups of buildings [12].…”
Section: Related Workmentioning
confidence: 99%
“…The existing research on tangible interaction with CAD, such as [9][10] and the recent DeskCube by Autodesk Research [11] demonstrated tangible interfaces which are limited merely to perform navigation and modify viewpoints in CAD.The Luminous Planning table by MIT Media Lab and School of Architecture and Planning was developed for urban simulation [12].The integration between the physical building models and the digital drawing, plans and models allows real-time simulation of sun, wind, and shade being projected on the physical models located on the table.The building models can be moved or rotated to generate real-time feedback of the impact of the variations. However, the physical-digital integration is not feeding into parametric design software, and therefore the modification of the model is limited to changing the location and orientation of the buildings.To our knowledge, the use of tangible interaction, physical sensing, and Web2.0 as part of the tool and medium for parametric design has not been previously addressed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout our own research and educational work, we have been applying VR in design support tools (e.g. de Vries et al 2003) and design projects (Achten and Turksma, 1999) on a regular basis. Additionally we observe a trend that students and architects turn to game-engines for VR-like studies and presentations (e.g.…”
Section: Introductionmentioning
confidence: 99%